Critical Care Management of the Patient with Clostridioides difficile. Issue 1 (January 2021) - Adelman, Max W.; Woodworth, Michael H.; Shaffer, Virginia O.; Martin, Greg S.; Kraft, Colleen S.
Abstract : OBJECTIVES: To review published clinical evidence on management of Clostridioides difficile infection in critically ill patients. DATA SOURCES: We obtained relevant studies from a PubMed literature review and bibliographies of reviewed articles. STUDY SELECTION: We selected English-language studies addressing aspects of C. difficile infection relevant to critical care clinicians including epidemiology, risk factors, diagnosis, treatment, and prevention, with a focus on high-quality clinical evidence. DATA EXTRACTION: We reviewed potentially relevant studies and abstracted information on study design, methods, patient selection, and results of relevant studies. This is a synthetic (i.e., not systematic) review. DATA SYNTHESIS: C. difficile infection is the most common healthcare-associated infection in the United States. Antibiotics are the most significant C. difficile infection risk factor, and among antibiotics, cephalosporins, clindamycin, carbapenems, fluoroquinolones, and piperacillin-tazobactam confer the highest risk. Age, diabetes mellitus, inflammatory bowel disease, and end-stage renal disease are risk factors for C. difficile infection development and mortality. C. difficile infection diagnosis is based on testing appropriately selected patients with diarrhea or on clinical suspicion for patients with ileus. Patients with fulminant disease ( C. difficile infection with hypotension, shock, ileus, or megacolon) should be treated with oral vancomycin and IV metronidazole, as well as rectal vancomycin in case of ileus. Patients who do not respond to initial therapy should be considered for fecal microbiota transplant or surgery. Proper infection prevention practices decrease C. difficile infection risk. CONCLUSIONS: Strong clinical evidence supports limiting antibiotics when possible to decrease C. difficile infection risk. For patients with fulminant C. difficile infection, oral vancomycin reduces mortality, and adjunctive therapies (including IV metronidazole) and interventions (including fecal microbiota transplant) may benefit select patients. Several important questions remain regarding fulminant C. difficile infection management, including which patients benefit from fecal microbiota transplant or surgery.